MySQL cookbook - DuBois, Paul (O'Reilly Media, 2014)
When you need quick solutions or techniques, this handy resource provides scores of short, focused pieces of code, hundreds of worked-out examples, and clear, concise explanations. Ideal for beginners and professional database and web developers, this updated third edition covers powerful features in MySQL 5.6 (and some in 5.7)